Analisis Collaborative Governance dalam Implementasi Kebijakan Penerimaan Peserta Didik Baru (PPDB) di SD Negeri Palembang - Mawaddah; Rizki Yolanda; Muslim; Een Endasari; Milsani Ramkita (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the implementation of the online-based New Student Admission (PPDB) policy at SD Negeri 20 Palembang from the perspective of collaborative governance. The research uses a qualitative approach with a descriptive analytical type. The informant determination technique is carried out using purposive sampling involving the Palembang City Education Office, the school principal, the PPDB committee, and parents of students. Data collection is conducted through in-depth interviews, observation, and documentation. The data analysis technique uses the Miles and Huberman interactive model, which includes data reduction, data presentation, and drawing conclusions. The validity of the data is tested through source triangulation and method triangulation. The research results indicate that the implementation of the PPDB policy at SD Negeri 20 Palembang has not been running optimally, although administratively it has complied with the applicable regulations. The success of digital-based education policies is influenced by technological readiness, regulations, society, and collaborative governance. The study is still limited to one elementary school and focuses more on collaborative governance, so the socio-economic aspects and the evaluation of the digital PPDB system have not been thoroughly examined. Future research is recommended to involve more schools, use mixed methods, and examine digital transformation and the quality of education services. This study also recommends increasing policy socialization, digital literacy, technology access, and collaboration between the government, schools, and the community.